Plasma Catestatin Levels and Advanced Glycation End Products in Patients on Hemodialysis - Mirko Luketin; Maja Mizdrak; Dijana Boric-Skaro; Dinko Martinovic; Daria Tokic; Marino Vilovic; Daniela Supe-Domic; Tina Ticinovic Kurir; Josko Bozic (Biomolecules, 2021)
Catestatin (CST) is a pleiotropic peptide involved in cardiovascular protection with its antihypertensive and angiogenic effects. Considering that patients with end-stage renal disease (ESRD) who are undergoing hemodialysis (HD) are associated with higher cardiovascular risk, the aim of this study was to investigate plasma CST levels in HD patients, compare them to healthy controls and evaluate possible CST associations with advanced glycation end products (AGEs) and laboratory, anthropometric and clinical parameters. The study included 91 patients on HD and 70 healthy controls. Plasma CST levels were determined by an enzyme-linked immunosorbent assay in a commercially available diagnostic kit, while AGEs were determined using skin autofluorescence. Plasma CST levels were significantly higher in the HD group compared to the controls (32.85 ± 20.18 vs. 5.39 ± 1.24 ng/mL, p < 0.001) and there was a significant positive correlation between CST and AGEs (r = 0.492, p < 0.001). Furthermore, there was a significant positive correlation between plasma CST levels with both the Dialysis Malnutrition Score (r = 0.295, p = 0.004) and Malnutrition-Inflammation Score (r = 0.290, p = 0.005). These results suggest that CST could be playing a role in the complex pathophysiology of ESRD/HD and that it could affect the higher cardiovascular risk of patients on HD.